Estimation of Extravascular Lung Water During and After Extensive Thoracic Interventions - V. V. Kuzkov; M. M. Orlov; D. A. Kryuchkov; E. V. Suborov; L. J. Bjertnas; M. Yu. Kirov (Общая реаниматология)
Background. Postoperative lung injury is a cause of most fatal outcomes after extensive lung resections. Death rates due to postpneumonectomy pulmonary edema have remained unchanged within the past 20 years and are currently tending to 100%. Objective: to make prolonged lung edema monitoring in patients after extensive thoracic interventions. Subjects and methods. The observational study covered 27 patients who had undergone pneumonectomy (PE) (n=16) or lung resection (n=11). Invasive monitoring by the PiCCOplus system was performed to examine the systemic and pulmonary hemodynamics of all the patients during surgery and within 48 postoperative hours. Results. PE rather than lung resection was accompanied by a significant reduction in the extravascular lung water index (EVLWI). Most patients who had undergone PE were found to have a subclinical increase in EVLWI 36-48 hours after termination of the intervention. Conclusion. In this observational clinical study, isolated thermodilution showed an immediate decrease in EVLWI after PE and its increase at 36—48 postoperative hours. Lobar or segmental interventions failed to cause significant changes in EVLWI in the perioperative period. Key words: pneumonectomy, lung resection, lung edema, extravascular lung water, acute lung injury.